A LEGAL REVIEW OF GOVERNMENT REGULATION NO. 34 OF 2019 ON BORDER TRADE IN RELATION TO LEGAL PROTECTION FOR INDONESIA’S BORDER COMMUNITIES - Irma Rachmawati Maruf; Karman (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Indonesia’s border regions require clear legal regulations to ensure certainty and protection for the communities living in these areas. This study aims to critically analyse Government Regulation No. 34 of 2019 on Border Trade in the context of legal protection for Indonesia’s border communities. The research method employs a normative legal approach, utilising legislative and conceptual analyses. The findings indicate that Government Regulation No. 34 of 2019 has provided a comprehensive regulatory framework establishing the legal subjects, locations, administrative requirements, types of goods, and transaction values for border trade. This regulation provides preventive legal protection by affirming the rights of border communities to engage in trade, establishing official border crossing routes, and regulating immigration and customs documentation—which are prerequisites for the legality of economic activities. However, the effectiveness of this legal protection remains limited, as the implementation of the regulation on the ground faces challenges such as inter-agency coordination issues, resource constraints, and poor public access to public services. This study recommends the need for a holistic and synergistic approach involving central and local governments, the enhancement of border infrastructure capacity, legal awareness programmes for the community, and a shift in policy orientation from security to the fulfilment of constitutional rights and the welfare of border communities.